Pengaruh Faktor Sosial Ekonomi terhadap Perilaku Kriminalitas (Tinjauan Literatur) - Adri, Sandy; Karimi, Syafruddin; Indrawari, Indrawari (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2019)
This article reviews a number of factors underlying personal motives to commit crime in order to reveal some socio-economic characteristics attributed with criminal behaviours. It would be beneficial to clarify the spheres in which the state may interfere to prevent and overcome crime actions with a correct knowledge to surpress the tendencies of certain social groups to commit crime or be criminalized. The state has been resolving crime issues by adding police officers, prosecutors and prison cells to ensure punishment. However, proper education along with the enhancement of its resources are now urgent to improve legal awareness which is the essential key of crime prevention. In the end, the criminology perpective on criminal behaviours remains complex since more information on subject's background and history need to be elaborated. A uniform treatment for diverse socio-economic situation is absurd while improving family and environmental wellbeings seem to promise reduction of individual tendency against the law.